The construction of environmental indicators for determination of performance of ESG indicators to support decision-making of investors - Kocmanová, Alena; Karpíšek, Zdeněk; Klímková, Markéta (Business: Theory and Practice, 2012)
This contribution deals with the construction of environmental indicators, serving investors for the assessment of complex performance of companies in accordance with social and corporate governance indicators, the so-called ESG performance indicators. The research project “Construction of Methods for Multifactor Assessment of Company Complex Performance in Selected Sectors”, solved by the team of authors has been introduced. In recent years, investment managers have preferred the importance of ESG indicators showing long-term sustainable performance of those companies in which they have invested their financial resources. The objective of presented contribution is the proposal of environmental indicators, i.e. key ESG performance indicators. Environmental indicators are used not only for decision-making, but also for determination of sustainable value. A number of successive steps have been taken to construct environmental indicators and a combination of various statistical methods has been employed. An empirical analysis of environmental performance indicators for the companies operating in the processing industry according to CZ-NACE has been carried out on the basis of the analysis of sources, suggested by international organisations and voluntary environmental instruments. Environmental performance indicators, facilitating investors to decide on their investment activities and forming the part of key ESG-performance indicators, represent expected results of the empirical research.